DEVELOPMENT OF FUTSAL BASIC TECHNIQUE TRAINING MODEL FOR BEGINNER BASED ON PLAYING METHODS - Febi Kurniawan; Apta Mylsidayu (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
AbstractThe objective of this study is to create a development of futsal basic technique training model for beginner based on valid and reliable play method that is tailored to player’s demand in order to be more convenient for the coach to train futsal by using manual. This research uses quantitative and qualitative approach by using research and development method of Borg and Gall model consisting of 10 stages. The result of this research shows that the product of this development of futsal basic technique training model for beginner based on playing method is nothing to be revised fundamentally, all the indicators have met the standard and feasible to be used, and then the final result on the development of the training manual, so the product developed by researcher can be used as a reference for players or coaches because it can be used as a guidance to increase the effectiveness of futsal basic technique exercise process, besides, the players and coaches are able to obtain various futsal basic technique training based on various playing methods.Keywords: Model, training, basic technique, futsal, beginner player, playing method.